Renal Sodium Handling in Children with Nephrotic Syndrome (Ibrahim Cardiac Medical Journal, 2015)
Background and Objectives: Neprhrotic Syndrome (NS) is a predictable complex with severe, prolonged increase in glomerular permeability for protein leading to hypo-albuminemia. Edema is the other major abnormality; but the underlying mechanism is incompletely resolved. Again during edema formation stage, some of these children express clinical symptoms of hypovolemia, while others do not. The purpose of the study was to identify the NS-children with hypovolemia by measuring the parameters of renal function in respect to their specificity and easy availability.Methods: We studied renal function in 17 children with NS in full blown nephrosis who had come to the Nephrology-Follow up Clinic or the OPD in Dhaka Shishu (Children) Hospital (DSH) and got admitted into the hospital as nephrotic patients with relapses or 1st episodes. The period of study was July 2001 to December 2001 for total period of 6 months. Findings were related to presence or absence of symptoms suggestive of hypovolemia, and were compared to results of similar studies in the same children in remission.Results: Nine children presented with hypovolemic symptoms, and 8 without such symptoms. Both groups displayed severe proteinuria, hypo-albuminemia and edema. Twelve (70.5%) children showed higher blood pressure values in comparision to those of remission. Symptomatic patients showed tendency for a low glomerular filtration rate (GFR), and significantly impaired urine dilution, lower urine-sodium (UNa/Ucr), decreased fractional sodium excretion (FENa), and elevated sodium-potassium exchange quotient, UK/(UK+UNa). In the non-symptomatic patients, these parameters were normal.Conclusions: Among parameters of renal functions,UK/(UK+UNa)-sodium-potassium exchange quotient was found to be the most specific - higher values in hypovolemic patients and lower in patients with stable edema, and in remission too.Ibrahim Cardiac Med J 2013; 3(1&2): 15-20